From Twisted Quantum Loop Algebras to Twisted Yangians - Conner, P.; Guay, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
We prove how the Yangian of glN in its RTT presentation and Olshanski's twisted Yangians for the orthogonal and symplectic Lie algebras can be obtained by a degeneration process from the corresponding quantum loop algebra and some of its twisted analogues.